SOSIALISASI PEMBUATAN JAMU KEKINIAN DAN JAMU INSTAN DI DUSUN KADIBESO, ARGODADI, SEDAYU, BANTUL, DIY - Fatmawati, Annisa (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
The people in Kadibeso Hamlet, Argodadi Village, Sedayu, Bantul, have never received socialization and training on making instant herbal medicine. The methods used in conducting the socialization and workshop on making instant herbal medicine to the people of Dusun Kadibeso: counseling on